On some methods of solving one-variable inequalities involving modulus notation - Kimsanova Muhayyoxon Rustamjon qizi; Jorayev Sh.Yu. (Researchparks Publishing, 2023)
The methods of solving equations and inequalities involving the modulus symbol are somewhat fewer and more difficult, and students are more interested in learning the easier methods of solving them. One such method is the interval method.